Growth of Pioneer Grasses in Monoculture and Polyculture Systems of Hydroseeding Applied in a Coal Mining Tailing from the South Kalimantan - Rahma, Amalia Fadhila; Arisoesilaningsih, Endang (Biotropika: Journal of Tropical Biology, 2015)
ABSTRACT Â The aims of this research were to compare germination of local and pioneer grasses seeds sown in garden soil and hydroseeding mulch. Furthermore, we also observed growth, density and coverage of the grasses planted in monoculture or polyculture systems applied in a post coal mining tailing from the South Kalimantan. Species used were Eleusine indica (L.), Paspalum conjugatum P.J.Bergius, Sporobolus indicus (L.) R.Br. and Eulalia amaura (Buese) Ohwi. Thirty two seeds of each grass were sown on a garden soil and mulch of hydroseeding to observe rate and time of germination. The seds of each species (in monoculture treatment) and composited species (in polyculture treeatment) were then mixed with mulch and spreaded above the coal mining tailing put in plastic pot. Each treatment were replicated 3 to 5 times. The observed variables were the time and rate of germination,Â density, maximum length of leave blade, plant height and coverage, root/shoot length ratio. Data were analyzed descriptively and statistically using one way Anova, Brown Forsythe or t tests, cluster and biplot analysis. Results of research showed that seeds of all pioneer grasses sown in monoculture germinated in both media, garden soil and hydroseeding mulch. Otherwise, E. indica and E. amaura seeds were less germinated in polyculture system. In monoculture system, germination rate of seeds sown on theÂ soil was higher, moreover seeds rapidly germinated rather than those of hydroseeding mulch. Density, growth and coverage of monoculture grass tent higher than polyculture ones. Root system of all species developed well in the mining tailing, therefore its grew longer than their shoot. Key word : Coal mining tailing, germination, hydroseeding, pioneer grasses